2021
DOI: 10.3390/ph14060588
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Piplartine against LPS-Induced Sepsis through Attenuating the MAPKs/NF-κB Signaling Pathway and NLRP3 Inflammasome Activation

Abstract: Piplartine (or Piperlongumine) is a natural alkaloid isolated from Piper longum L., which has been proposed to exhibit various biological properties such as anti-inflammatory effects; however, the effect of piplartine on sepsis has not been examined. This study was performed to examine the anti-inflammatory activities of piplartine in vitro, ex vivo and in vivo using murine J774A.1 macrophage cell line, peritoneal macrophages, bone marrow-derived macrophages and an animal sepsis model. The results demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…After macrophages were treated with proinflammatory stimuli, NO and PGE2 were generated from iNOS and COX-2, respectively. In addition, cPLA2 phosphorylation was involved in COX-2-dependent PGE2 generation in macrophages [19,34]. This result is the first to demonstrate that 1-NP-induced NO generation occurs through iNOS upregulation and PGE2 production by the upregulation of COX-2 through cPLA2 phosphorylation.…”
Section: Discussionmentioning
confidence: 77%
“…After macrophages were treated with proinflammatory stimuli, NO and PGE2 were generated from iNOS and COX-2, respectively. In addition, cPLA2 phosphorylation was involved in COX-2-dependent PGE2 generation in macrophages [19,34]. This result is the first to demonstrate that 1-NP-induced NO generation occurs through iNOS upregulation and PGE2 production by the upregulation of COX-2 through cPLA2 phosphorylation.…”
Section: Discussionmentioning
confidence: 77%
“…Both MAPK and NF-κB signaling pathways are known to drive inflammation-associated gene expressions during LPS-induced inflammation. 24 , 25 To assess whether punicalagin regulated the activation of MAPK and NF-κB signaling pathways by LPS-induced BV2 cells, cells were pre-treated with various doses of punicalagin (0 to 100 μM) for 30 min following 1 μg/mL LPS treatment for 6 h. The expression of phospho-ERK, ERK, phospho-JNK, JNK, phospho-p38, and p38 was examined by Western blot. As shown in Figure 3A–D , punicalagin significantly decreased the phosphorylation of ERK, JNK, and p38 in LPS-induced BV2 cells in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“… 23 In addition, the MAPK cascade and NK-κB signaling pathway both regulate the expression and production of LPS-induced proinflammatory cytokines. 24 NF-κB has been demonstrated to play an integral role in the progression of Alzheimer’s disease 44 and ischemic stroke. 45 A previous murine model in vivo and in vitro study revealed the anti-neuroinflammatory effect of punicalagin on microglia and astrocytes by inhibiting the production of proinflammatory cytokines including IL-1β, IL-6 and TNF-α and interfering with NF-κB signaling via binding to its subunit p50 directly.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the prognosis of HBV-HCC patients, we screened 13 small molecule compounds using the CMap database. Piperlongumine can reduce colitis-associated colorectal cancer ( 40 ) and relieve sepsis by attenuating the activation of inflammasomes ( 41 ). From the enrichment results, piperlongumine acts on the HIF-1 signaling pathway and lyase activity, while fisetin regulates NF-kB transcription factor activity.…”
Section: Discussionmentioning
confidence: 99%